3-D finite-element analysis of fiber-reinforced soft bending actuator for finger flexion - Mohd. Faudzi, Ahmad Athif (2013)
Towards the development of a safe, small, lightweight and human-friendly finger exoskeleton, device made from high elasticity material driven by pneumatic source; or simply known as soft actuator is currently being paid to attention. The study is to determine the optimum fiber-reinforced elastic soft actuator model to be employed in an exoskeleton for finger rehabilitation. Bending motion anticipated from a 3-D finite element actuator model is verified in the nonlinear finite element software, MARC™. The effectiveness of the proposed model is discussed based on the displacement data obtained from the large strain finite element analysis. Specific geometric properties, material properties, contact and boundary conditions related to the real experimental testing were applied to the analysis. Based on the results, the proposed model shows a good presentation of bending motion at applied pressure of 150 kPa. The behavior of bending motion which is greatly influenced by the angle of the fiber reinforced to the actuator is also discussed.